Cascade of care of people diagnosed with HIV in New Zealand between 2006 and 2017. Issue 2 (27th October 2020) - McAllister, S; van Asten, H; Anglemyer, A; Crengle, S; Zeng, J; Raymond, N; Handy, R; Giola, M; Dickson, N; Priest, P
Abstract : Objectives: We estimated the proportion of people reported with HIV in New Zealand between 2006 and 2017, and alive in 2017–2019, who were on antiretroviral therapy (ART) and had a suppressed viral load (VL), and explored their associated characteristics. Methods: Data were anonymously linked to information on ART and VL within the data collection period (January 2017 to August 2019) using the National Health Index (NHI), Ministry of Health and laboratory datasets, as well as information from clinical specialists. Logistic regression was used to test for associations. Sensitivity analyses were undertaken to estimate the range for the key proportions. Results: Overall, 2355 people were reported with HIV, of whom 116 (5%) had died, 337 (14%) were overseas, and 1701 (72%) were alive in New Zealand; for the remaining 201 (9%) the outcome was unknown. Clinical data were available for 1490 people (87.6%): 1408 (94.5%) were on ART, 11 (< 1%) were not on ART, and for 71 (4.8%) this was unknown. Of those on ART, 1156 (82.1%) had a suppressed VL (< 200 copies/mL), 34 (2.4%) were unsuppressed, and for 218 (15.5%) this was unknown. The estimate of the proportion on ART ranged from 99% to 78%, and those with a suppressed VL ranged from 98% to 78%. Conclusions: Among people with HIV in New Zealand who are under care, a high proportion were on ART and had suppressed VL. Increasing collection of NHIs and better linkage with laboratory information will reduce the number with unknown information and provide more complete VL results in the future.